PENINGKATAN HASIL BELAJAR PENARIKAN AKAR SEDERHANA DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) DI KELAS V SD NEGERI - Prima, Ade (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is motivated learning outcomes are low drawdown simple roots. For that we need an increase in learning outcomes RME approach that emphasizes student experience gained from real-world, aims to describe the increase of learning outcomes withdrawal simple roots, with the planning, implementation, observation and reflection. The study was conducted in two cycles, the first cycle and second cycle, the cognitive aspects of learning outcomes shows the first cycle an average of 7.25, the second cycle average of 8.7, affective first cycle an average of 7.8 second cycle average 9, and psychomotor first cycle average of 7.9, the second cycle average of 8.9. RPP assessment score of 78.5% first cycle, cycle II score of 89%, the first cycle of teacher activity score of 73%, 85.5% cycle II scores, student activity score of 79% first cycle, cycle II score of 89.5. Mastery of learning outcomes first cycle and an average of 7.7 to 8.9 second cycle. Concluded RME approach is to improve learning outcomes. Kata Kunci : hasil belajar, akar sederhana, RME